Assessing the effectiveness of a semi-annual monitoring model for data analysis and use in routine immunisation in Benin - Lamidhi Salami; Yolaine Glele Ahanhanzo Hessou; Jean Pierre de Lamalle; Alphonse Biaou; Moussiliou Noël Paraïso (Intelektual Pustaka Media Utama, 2026)
Routine immunisation programmes generate large volumes of data, yet their effective analysis and use for decision-making remain limited at the operational level. For over three decades, Benin has institutionalized a semi-annual monitoring system to assess effectiveness, quality, and develop problem resolution plans (PRPs). This study evaluated its effectiveness in fostering data analysis and use within vaccination services. A descriptive cross-sectional study using mixed methods was conducted from January to June 2025 in eleven health centers across four departments. Data collected via direct observation, semi-structured interviews (n = 38), and document review underwent descriptive and qualitative analysis. Input availability and service accessibility remained optimal (100%). Variability persisted in utilisation, continuity, and quality, with recurrent over-coverage rates. During self-monitoring, technical tasks were frequently performed, whereas in-depth analysis and PRP development were limited (9.09%). Although 90.9% of centers had PRPs, their quality was mostly acceptable, with low innovation and weak follow-up mechanisms. Community participation was irregular. Nevertheless, 81.82% of managers perceived PRPs as contributing to improved vaccination performance. Semi-annual monitoring remains functional and relevant; however, strengthening analytical capacity, digital tools, follow-up mechanisms, and community engagement is essential to institutionalise a sustainable culture of data use for decision-making.